2014
DOI: 10.1177/875687051403300205
|View full text |Cite
|
Sign up to set email alerts
|

Secrets of Successful Grant Writing to Support Rural Special Education Programs

Abstract: This article explains the process of identifying grant funding sources and writing a grant proposal and attempts to demystify the process as it relates to grant funding in special education and disability services. It offers a series of simple steps to help new or less experienced grant writers in locating funding agencies, reading and understanding the request for proposals, and preparing a competitive proposal. Each step includes suggestions for how anyone can become a more successful grant writer and reach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In preparing the budget, it is suggested that novice researchers should review the application budgets of colleagues and mentors [16]. Novice grant writers should get help with budget preparation, together with other grant application activities, such as legal, contractual, intellectual property, biosafety and ethics [2]. About 54% of researchers rated ethical considerations as the most important, and a few experienced researchers reported ethical problems with grant reviewers in previous applications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In preparing the budget, it is suggested that novice researchers should review the application budgets of colleagues and mentors [16]. Novice grant writers should get help with budget preparation, together with other grant application activities, such as legal, contractual, intellectual property, biosafety and ethics [2]. About 54% of researchers rated ethical considerations as the most important, and a few experienced researchers reported ethical problems with grant reviewers in previous applications.…”
Section: Discussionmentioning
confidence: 99%
“…and (5) environment: is the institution supportive, and are the resources adequate for the project? [2,5,6]. According to the United Kingdom Medical Research Council (UK-MRC), the key components of the assessment criteria used by grant agency panels are usually based on research quality (scientific rationale, novelty, importance, and timeliness of the research), research management, and people (suitability of the investigator group, including the track record(s) of the individuals in the study team), methodology (feasibility of experimental plans, statistics, methodology, and design) [7].…”
Section: Online Structured Questionnairementioning
confidence: 99%
See 1 more Smart Citation